Effects of Interictal Epileptiform Discharges on Cognition - Meekes, Joost; Jennekens-Schinkel, Aag (Journal of Pediatric Epilepsy, 2018)
Interictal epileptiform discharges (IEDs) are brief events (typically < 1 second, although some authors use a cutoff of up to 3 seconds) in the electroencephalogram (EEG), which are not accompanied by any overt change in behavior or consciousness. IEDs are associated with both chronic cognitive deficits and transient cognitive impairment (TCI). Higher IED load correlates with lower intelligence quotient (IQ) and poorer performance on tests of memory and executive function. TCI has mainly been observed during tasks that place high demands on attention, visuomotor speed, and working memory. There is evidence that IEDs may also directly interfere with episodic memory. Despite the evidence for associations between IEDs and cognitive dysfunction, there is currently scant evidence that IEDs, in fact, cause chronic cognitive deficit in humans. Although causality appears likely in the case of TCI, even here the conditions under which IEDs affect cognition are unclear. The evidence in favor of treating IEDs with medication is very limited. Attempts to treat IEDs should only be made when it is clear that cognitive impairment interferes with activities or participation. Such attempts require strong single-case designs and careful monitoring of both the EEG and cognitive function to establish the efficacy of treatment in individual patients.
Keywords: interictal epileptiform discharges; transient cognitive impairment; nonictiform discharges